2021
DOI: 10.1111/1556-4029.14747
|View full text |Cite
|
Sign up to set email alerts
|

Secondary traumatic stress, burnout, compassion satisfaction, and perceived organizational trauma readiness in forensic science professionals

Abstract: Secondary traumatic stress, burnout, and compassion satisfaction have been described since the 1980s and extensively studied in first responders, law enforcement, legal professionals, and human service providers. There are few studies in forensic science professionals. To determine levels of secondary traumatic stress, burnout, and compassion satisfaction and relate these to demographics and job characteris- Highlights• Research on secondary traumatic stress, burnout, and compassion satisfaction is limited in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…Corroborating these points, Charlton et al (2010) found that many fingerprint examiners held a strong fear of making mistakes and/or a strong desire to reach definitive conclusions (i.e., need for closure). Most recently, Almazrouei et al (2020; found that many examiners reported high levels of workplace-related stress-and 39% felt that stress influenced their performance (see also Levin et al, 2021). To mitigate any negative effects of stress on performance, Jeanguenat and Dror (2018) proposed that forensic labs take concrete steps to promote healthy work-life balance, such as offering flexible schedules, healthy nutrition, exercise initiatives, and mindfulness trainingall of which have proven beneficial to employees in other domains.…”
Section: Organizational Factorsmentioning
confidence: 99%
“…Corroborating these points, Charlton et al (2010) found that many fingerprint examiners held a strong fear of making mistakes and/or a strong desire to reach definitive conclusions (i.e., need for closure). Most recently, Almazrouei et al (2020; found that many examiners reported high levels of workplace-related stress-and 39% felt that stress influenced their performance (see also Levin et al, 2021). To mitigate any negative effects of stress on performance, Jeanguenat and Dror (2018) proposed that forensic labs take concrete steps to promote healthy work-life balance, such as offering flexible schedules, healthy nutrition, exercise initiatives, and mindfulness trainingall of which have proven beneficial to employees in other domains.…”
Section: Organizational Factorsmentioning
confidence: 99%
“…In a 2021 study of U.S. crime laboratories and medical examiner offices, Levin et al found that in‐person interactions, such as scene investigation and direct encounters with victims, increased the likelihood of secondary traumatic stress or vicarious traumatization [18]. In the context of SUID, law enforcement bear the weight of additional stressors not encountered by forensic professionals represented in this study.…”
Section: Discussionmentioning
confidence: 92%
“…In addition to challenges created by lack of preparation, participants revealed that the overwhelming emotions encountered at infant death scenes further impacted their ability to contribute ef- tional challenges [18]. A United Kingdom study of law enforcement warned that investigative experience may not protect against cognitive and emotional effects of homicide investigation and that such stressors may result in flawed decision-making [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study of medicolegal death investigators and forensic pathologists [29] and one study of medicolegal death investigators with other laboratory forensic scientists [30] examined mental health wellness. Miner, Markowitz, Peterson, and Weston's approach was unique in that the researchers used language processing tools to identify trends in how medicolegal death investigators and forensic pathologists documented sudden unexpected deaths [29].…”
Section: Mental Health/emotional Stressmentioning
confidence: 99%